A Novel Regulation of K-antigen Capsule Synthesis in Porphyromonas gingivalis Is Driven by the Response Regulator PG0720-Directed Antisense RNA - Kim, Hey-Min; Ranjit, Dev K.; Walker, Alejandro R.; Getachew, Heran; Progulske-Fox, Ann; Davey, Mary E. (Frontiers in Oral Health, 2021)
The periodontal pathogen Porphyromonas gingivalis strain W83 displays at least three different surface glycans, specifically two types of lipopolysaccharides (O-LPS and A-LPS) and K-antigen capsule. Despite the importance of K-antigen capsule to the virulence of P. gingivalis, little is known as to how expression of genes involved in the synthesis of this surface glycan is regulated. The genes required for K-antigen capsule synthesis are located in a locus that encodes a number of transcripts, including an operon (PG0104 to PG0121, generating ∼19.4-kb transcript) which contains a non-coding 77-bp inverted repeat (77bpIR) region near the 5'-end. Previously, we identified a 550-nucleotide antisense RNA molecule (designated asSuGR for antisense Surface Glycan Regulator) encoded within the 77-bpIR element that influences the synthesis of surface glycans. In this study, we demonstrate that the DNA-binding response regulator PG0720 can bind the promoter region of asSuGR and activate expression of asSuGR, indicating that PG0720 may indirectly influence transcript levels of the K-antigen capsule operon expressed from the sense strand. The data show that deletion of the PG0720 gene confers a defect in the presentation of surface polysaccharides compared with the parent strain and quantitative RT-PCR (qPCR) analysis determined that the overall expression of genes involved in K-antigen capsule synthesis were down-regulated in the PG0720 mutant. Furthermore, the defects of the PG0720 deletion mutant were restored by complementation. Importantly, the PG0720 deletion mutant showed reduced virulence. Altogether, our data show that the response regulator PG0720 regulates expression of asSuGR, a trans-acting antisense RNA molecule involved in modulating the production of surface polysaccharides in P. gingivalis strain W83. The data provide further evidence that surface glycans are key virulence determinants and significantly advances our understanding of the molecular mechanisms controlling the synthesis of P. gingivalis K-antigen capsule, a key virulence determinant.